A Study on the Characteristic Features of Covid-19 Deaths in a Regional Hospital in Mthatha in the Eastern Cape, South Africa - Kaswa RP; B Meel (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Covid-19 is an acute health emergency to human beings all over the world. This pandemic has destabilised the day-to-day life of almost everyone. It is a challenge to scientists and politicians to initiate a return to normal human life from the grip of Covid-19 so that the economies of countries do not stop growing.Objective: To study the characteristics of Covid-19 deaths in a regional hospital in Mthatha in the Eastern Cape, South Africa.Method: It is a retrospective record review study of the cases of patients in Mthatha Regional Hospital (MRH) in South Africa who were not able to be saved.Results: There were 100 deaths in MRH. Of these 57 (57%) were females and 43 (43%) males. The average age was 63.3 years. Shortness of breath was the most common presenting symptom followed by weakness, a cough and fever. More than half of the Covid-19 cases had associated co-morbidity such as hypertension (50%), diabetes (37%) and HIV (15%). The mean oxygen saturation (SpO2) at the time of admission was 75.5±17 on pulse oximetry. Conclusion: The covid-19 mortality was 1.3 times higher among females in the regional hospital under study. The majority of the victims were suffering hypertension and diabetes.